A Potential Role for CXCR2 in Early-onset Preeclampsia: Placental CXCR2 Expression is Related to Increased Blood Pressure and Serum LDH Levels. Issue 3 (23rd July 2020) - Zhang, Yan-Ping; Liu, Xi-Jing; Jia, Jin; Wang, Tao; Li, Li; Zhou, Rong
Abstract: Objective: This study was aimed to determine the changes in CXCR2 expression in preeclampsia placenta and its correlation with clinical parameters. Methods: Sixty-four gravidas ranging in age from 25 to 42 years referred to the obstetrics unit of the West China Second University Hospital from April 2012 to October 2012 were recruited in this case-control study; women were diagnosed and divided into early-onset preeclampsia group ( n = 22), late-onset preeclampsia group ( n = 22), and healthy pregnancy group ( n = 20). After immunolocalized in human placenta, the levels of CXCR2 protein and messenger ribonucleic acid (mRNA) were detected by enzyme-linked immunosorbent assay and real-time quantitative polymerase chain reaction. Correlations between placental CXCR2 protein expression with systolic blood pressure and lactate dehydrogenase (LDH) in early-onset preeclampsia were examined using Pearson or Spearman's correlation coefficients. Results: Placental CXCR2 protein and mRNA expression in early-onset preeclampsia was significantly lower than it was in placentas from healthy pregnancy pregnancies and late-onset preeclampsia ( P < 0.05). The placental CXCR2 protein expression correlated negatively with systolic blood pressure and LDH in early-onset preeclampsia ( r = −0.51, P < 0.05; r = −0.43, P < 0.05). Conclusion: Significant abnormal placental CXCR2 expression in early-onset preeclampsia, and its correlations with some clinical parameters (systolic blood pressure and LDH) were discovered, suggesting that CXCR2 may play a role in the pathogenesis of early-onset preeclampsia.